Allopregnanolone preferentially induces energy‐rich food intake in male Wistar rats. Issue 12 (11th December 2014) - Holmberg, Ellinor; Johansson, Maja; Bäckström, Torbjörn; Haage, David
Abstract Obesity is an increasing problem and identification of the driving forces for overeating of energy‐rich food is important. Previous studies show that the stress and sex steroid allopregnanolone has a hyperphagic effect on both bland food and palatable food. If allopregnanolone induces a preference for more palatable or for more energy‐rich food is not known. The aim of this study was to elucidate the influence of allopregnanolone on food preference. Male Wistar rats were subjected to two different food preference tests: a choice between standard chow and cookies (which have a higher energy content and also are more palatable than chow), and a choice between a low caloric sucrose solution and standard chow (which has a higher energy content and is less palatable than sucrose). Food intake was measured for 1 h after acute subcutaneous injections of allopregnanolone. In the choice between cookies and chow allopregnanolone significantly increased only the intake of cookies. When the standard chow was the item present with the highest caloric load, the chow intake was increased and allopregnanolone had no effect on intake of the 10% sucrose solution. The increased energy intakes induced by the high allopregnanolone dose compared to vehicle were very similar in the two tests, 120% increase for cookies and 150% increase for chow. It appears that in allopregnanolone‐induced hyperphagia, rats choose the food with the highest energy content regardless of its palatability.